The host actin cytoskeleton channels rhizobia release and facilitates symbiosome accommodation during nodulation in Medicago truncatula. Issue 2 (29th August 2018) - Zhang, Xiaxia; Han, Libo; Wang, Qi; Zhang, Chen; Yu, Yanjun; Tian, Juan; Kong, Zhaosheng
Summary: In plants, the actin cytoskeleton plays a central role in regulating intracellular transport and trafficking in the endomembrane system. Work in legumes suggested that during nodulation, the actin cytoskeleton coordinates numerous cellular processes in the development of nitrogen‐fixing nodules. However, we lacked live‐cell visualizations demonstrating dynamic remodeling of the actin cytoskeleton during infection droplet release and symbiosome development. Here, we generated transgenic Medicago truncatula lines stably expressing the fluorescent actin marker ABD2‐GFP, and utilized live‐cell imaging to reveal the architecture and dynamics of the actin cytoskeleton during nodule development. Live‐cell observations showed that different zones in nitrogen‐fixing nodules exhibit distinct actin architectures and infected cells display five characteristic actin architectures during nodule development. Live‐cell imaging combined with three‐dimensional reconstruction demonstrated that dense filamentous‐actin (F‐actin) arrays channel the elongation of infection threads and the release of infection droplets, an F‐actin network encircles freshly‐released rhizobia, and short F‐actin fragments and actin dots around radially distributed symbiosomes. Our findings suggest an important role of the actin cytoskeleton in infection droplet release, symbiosome development and maturation, and provide significant insight into the cellular mechanisms underlying nodule development and nitrogen fixation during legume–rhizobia interactions. Abstract : See also the Commentary on this article by Genre & Timmers, 221 : 611–613 .